Effectiveness of Recombinant Growth Hormone on The Growth of Java Barb (Barbonymus gonionotus) with Different Stocking Densities - Angraini, Siti Rena Yulia; Alimuddin, Alimuddin; Carman, Odang; Rahmi, Kurnia Anggraini (Universitas Gadjah Mada, 2025)
Tawes fish has economic value and affordable price. Growth rate and survival rate are important factors in cultivation productivity. The purpose of this study was to test the effectiveness of recombinant growth hormone of kertang grouper (rElGH) on the growth response of tawes fish seeds at different stocking densities. This study used a factorial randomized design with two treatment factors and three replications. The treatments were rElGH (dose 0 mg/kg and 2 mg/kg) and different stocking densities (40 fish/m3, 80 fish/m3 and 160 fish/m3). The tawes fish seeds used weighed 2.33 ± 0.002 cm and were 4-5 cm long. Maintenance is carried out for 60 days used a hapa measuring 1.0 × 1.0 × 1.0 m3 with a water height of ±60 cm. Fish are fed with at satiation method using commercial feed with a protein content of 31-33%. The administration of rElGH was carried out on the first 7 days of maintenance and continued with the provision of feed without rElGH. The results of the Two-way ANOVA analysis showed that the use of rElGH and stocking density and their interactions had significant differences. The best treatment was the provision of rElGH stocking density 40 (R40) with survival rate 100%, specific growth rate 3.58%/day, absolute weight gain 8.75 g, and feed conversion ratio 1.12. The combination of the use of rElGH and increasing stocking density significantly increased the biomass production of tawes fish.